Black holes: do they exist? - Malec, Edward (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Black holes entered scientific literature as early as at the end of eighteenth century. They had been known at that time as dark stars, but their concept did not find its way to physics or astronomy, and had been abandoned for more than one hundred years. I shall sketch historical developments and discuss present mathematical and observational status of black holes.